2017
DOI: 10.1051/0004-6361/201731318
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale environments of narrow-line Seyfert 1 galaxies

Abstract: Studying large-scale environments of narrow-line Seyfert 1 (NLS1) galaxies gives a new perspective on their properties, particularly their radio loudness. The large-scale environment is believed to have an impact on the evolution and intrinsic properties of galaxies, however, NLS1 sources have not been studied in this context before. We have a large and diverse sample of 1341 NLS1 galaxies and three separate environment data sets constructed using Sloan Digital Sky Survey. We use various statistical methods to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 109 publications
4
63
1
Order By: Relevance
“…If interaction, mostly minor mergers, indeed proves to be one of the dividing factors, this suggests that the observed heterogeneity of the NLS1 population might be due to their development over time. This also explains and supports the findings in Järvelä et al (2017) where NLS1 galaxies with jets were found to favour denser large-scale environments than NLS1 galaxies without jets. The probability of interaction, which might lead to the launching of a jet, is naturally higher in regions with more galaxies.…”
Section: Discussionsupporting
confidence: 89%
“…If interaction, mostly minor mergers, indeed proves to be one of the dividing factors, this suggests that the observed heterogeneity of the NLS1 population might be due to their development over time. This also explains and supports the findings in Järvelä et al (2017) where NLS1 galaxies with jets were found to favour denser large-scale environments than NLS1 galaxies without jets. The probability of interaction, which might lead to the launching of a jet, is naturally higher in regions with more galaxies.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results are found in various studies focusing on more powerful, radio-loud quasars (Ramos Almeida et al 2013;Chiaberge et al 2015;Olguín-Iglesias et al 2016). The fact that radio-loud NLSy1s are likely to be living in denser large-scale environments (Järvelä et al 2017) where mergers could be frequent, also provide supportive evidences for the merger triggered jet launching. Combining this with the idea of the young nature of NLSy1s, it can be concluded that γ-NLSy1 galaxies represent the beginning phase of the jet activity.…”
Section: Kinematic Age Of the Radio Jet And A Comparison With The Mersupporting
confidence: 87%
“…Black holes in NLSy1 galaxies usually grow via secular processes, develop pseudobulges, mostly remain radioquiet, and evolve to broad-line Seyfert 1s (Mathur 2000). Those residing in dense large-scale environments can frequently undergo mergers (Chiaberge et al 2015;Järvelä et al 2017), triggering rapid black hole growth due to inflow of gas driven by gravitational torques (Barnes & Hernquist 1991, and possibly spin-up the black hole leading to the launch of the relativistic jet. In this evolutionary scenario, γ-NLSy1s can be considered as nascent blazars and as such they are the best jetted systems to explore the jet launching regions and their associated physical processes.…”
Section: Discussionmentioning
confidence: 99%
“…In the future our aim is to increase the size of the sample, in order to have a better statistic. Furthermore, we will investigate the relation between the X-ray complexity and other potential inclination indicators, such as the [O III] line position ( [15], [3]) and ionization cones (e.g., [17], [6] and references therein), and other physical parameters of AGN such as Eddington ratio and large scale environment [11].…”
Section: Discussion and Future Workmentioning
confidence: 99%